Safety and feasibility of intranasal heroin-assisted treatment: 4-week preliminary findings from a Swiss multicentre observational study - Marc Vogel; Maximilian Meyer; Jean N. Westenberg; Adrian Kormann; Olivier Simon; Roba Salim Hassan Fadlelseed; Markus Kurmann; Rebecca Bröer; Nathalie Devaud; Ulrike Sanwald; Sophie Baumgartner; Hannes Binder; et al. (Harm Reduction Journal, 2023)
Abstract Background Heroin-assisted treatment (HAT) is effective for individuals with severe opioid use disorder (OUD) who do not respond sufficiently to other opioid agonist treatments. It is mostly offered with injectable diacetylmorphine (DAM) or DAM tablets creating a barrier for individuals who need the rapid onset of action but are either unable or unwilling to inject, or primarily snort opioids. To explore another route of administration, we evaluated the safety and feasibility of intranasal (IN) DAM. Methods This is a multicentre observational cohort study among patients in Swiss HAT. All patients planning to receive IN DAM within the treatment centres were eligible to participate. Participants were either completely switched to IN DAM or received IN DAM in addition to other DAM formulations or opioid agonists. Patients were followed up for four weeks. Sociodemographic characteristics, current HAT regimen, reasons for starting IN DAM, IN DAM doses, number of injection events in the sample, IN DAM continuation rate, and appearance of adverse events and nose-related problems were evaluated. Results Participants (n = 52) reported vein damage, preference for nasal route of administration, and desire of a stronger effect or for a less harmful route of administration as primary reasons for switching to IN DAM. After four weeks, 90.4% of participants (n = 47) still received IN DAM. Weekly average realised injection events decreased by 44.4% from the month before IN DAM initiation to the month following. No severe adverse events were reported. Conclusions After four weeks, IN DAM was a feasible and safe alternative to other routes of administration for patients with severe OUD in HAT. It addressed the needs of individuals with OUD and reduced injection behaviour. More long-term research efforts are needed to systematically assess efficacy of and patient satisfaction with IN DAM.